Danau Karya Village Community Education : Great vaccination, healthy community - sri rahayu (Borneo Community Development, 2022)
The government's program in administering vaccines to increase human immunity and break the chain of transmission from corona virus was followed by public concern about the impact of the vaccine. This information is of course obtained from sources that cannot be trusted. To prevent this, socialization related to vaccines was carried out, where this activity provided an overview of the safety and effectiveness of vaccination. This activity was attended by 10 residents of Danau Karya Village. The socialization was carried out by providing material through presentations and followed by discussions. This activity can open up public insight and knowledge about the importance of the Covid-19 vaccination